Pembuatan Komik Panduan Pemanfaatan Taman Bacaan Masyarakat Tanah Ombak Kota Padang - Hafshah, Siti; Nurizzati, Nurizzati (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
AbstractBased on the result of the research, it is concluded that the following matters. First, the community reading park Tanah Ombak built by Mr.Yusrizal KW, Mr. Syuhendri and Mr. Zurmailis has approximately 4000 copies of the book. The community reading park of Tanah Ombak is located in Purus III gang IV number 30 E. The reading park community of Â Tanah Ombak has 4 areas of activity named the field of creative writing, the field of art, the field of language, the field of mathematics. The reading park community of Tanah Ombak has 4 services, named (1) book lending service, (2) talent coaching service and child potency, (3) Service Cooperation with Various Parties (Partnership), (4) mobile library services. Secondly, After the data analyzed, the conclusion explains some steps of creating a comic utilization guide community reading park Tanah Ombak, named (1) Determine Topics or Themes,(2) Collect Information,(3) Determine the Text and Writing of the Text Story,(4) Making Comic Box,(5) Make a picture,(6) Make Conversation Texts and Balloons, and (7) Color Giving.Keywords: comic, TBM.